Images of Ideology and the Ideology of Imagery - Oestreicher, Richard (Labour / Le Travail, 1985)
The article reviews and comments on two books: "Mining Photographs and Other Pictures," by Robert Wilkie, Don Macgillivray, Allan Sekula, and Leslie Shedden, and "Voices from the Mountains," by Guy and Candie Carawan.
Keywords: CARAWAN, Candie; CARAWAN, Guy, 1927-2015; MINING Photographs & Other Pictures 1948-1968 (Book); Nonfiction; REVIEWS; SHEDDEN, Leslie; VOICES From the Mountains (Book); WILKIE, Robert; books